Perancangan Sistem Informasi Manajemen Stok Makanan dan Minuman pada RM. Lesehan Podomoro Berbasis Web dengan Metode Rapid Application Development - Eko Pras Setyo; Munawaroh (CV. Multi Kreasi Media, 2025)
Stock is a very crucial thing for companies whose business processes are directly related to goods. The restaurant is part of the company. There are times when the stock of food menus that are in high demand by customers cannot be ordered because they are out of stock. Often unnoticed, stock issues can cause losses for the company. Because there is no reference to determine the number of items to be stocked, restaurants often lack food stock, because the stock supply is still using estimates without data and analysis. RM stock management information system. Lesehan Podomoro is website-based, prioritizing developing a system in the menu mutation report section, this data can be processed for further stock analysis for the next day. The system designed can help the process of making reports and administration to be more effective and efficient. Making this system using the PHP 7.3 programming language and MySQL as the database, and the Apache application to run the web server. This application can be used to process data and stock management data reports.